Priorities in Movement Disorders Research - Mabel M. Macas; Criscely L. Go; Jose C. Navarro (Journal of Neurology, Neurological Science and Disorders - Peertechz Publications, 2015)
Objectives: To analyze the patterns of movement disorders prospectively using the registry of movement disorders in our institution and to identify some research priorities. Background and purpose: Movement disorders are common reasons for consultation and referrals in our hospital. They are often thought to affect movement only. However, most patients also experience psychiatric, cognitive, and other non-motor symptoms, either from the disease itself, or as a side-effect of medications. No data has been obtained regarding movement disorders in our institution. With the use of our registry, we aim to document findings prospectively, for use as data mining to support a variety of researches in the future, and to guide us as to priorities in services, teaching and research. Methods: Starting April 2014, all adult patients seen at the Department of Neurology and the Department of Behavioral Medicine both inpatients and outpatients, presenting with movement disorders, were included in our IRB-approved Movement Disorder Registry. With signed consent from these patients, the motor manifestations were documented by recording with a video camera. All verified movement disorders were included in this registry. These patients were then characterized as to their demographic and clinical profile, and were reviewed as to the pattern of movement disorders. Discussion: Since April 2014, we have registered about 41 patients, with a mean age of 51 years for male and 67 years for female. The most commonly seen movement disorder was Parkinson's disease (70%). Other movement disorders were dystonia, hemichorea, hemifacial spasm, tardive dyskinesia, and tic disorder. This was in keeping with other studies in Asian countries. As a national health institution, and the second institution locally with a registry of movement disorders, we hope to continue this registry so that we could obtain a substantial data for future researches, to establish a hospital prevalence and incidence of common movement disorders, and to be able to answer the possible natural course of movement disorders. Conclusion: Creating a registry of movement disorders is beneficial to be able to document findings from a prospective analysis the patterns of movement disorders in our institution and to help us construct research questions following research priorities in movement disorders. Among patients registered, Parkinson's disease remains the most common disease seen in our institution.